Allicin-induced cellular destruction of haemoflagellate protozoa, trypanosoma evansi in mice - Zainal-Abidin .B.A.H; Mohd. Shukri Hj. Baba (Universiti Kebangsaan Malaysia, 2011)
Allicin or diallyl thiosulfinate (C3H5SS(O)C3H5), an active compound of garlic (Allium sativum) is known for its pharmaceutical properties. In this study, the cellular destructive effects of allicin on a haemoflagellate protozoa parasite Trypanosoma evansi was investigated. Groups of male ICR mice were infected with a lethal dose of the parasite (1×105 parasites per mouse) and each group was either treated intraperitoneally with berenil (0.01 mL per mouse, a commercial anti-trypanosomal drug) on D+3 post-infection as the positive control group, treated orally with allicin (0.1 mL of 15 μg/mL allicin solution per mouse) for 30 days starting from D-7 pre-infection as the experimental group, or left untreated as the negative control group. Thin-stained blood smears were prepared from each mouse every alternate day, starting from D+3 post-infection and continued until the animal succumbed or until D+90 post-infection. Parasitaemias were determined using light microscope. Unstained blood smears were also prepared for direct observation under Phillips XL30 and Leo 1450VP scanning electron microscopes. All mice in the negative group succumbed to the infection with drastic increase of parasitaemias while all the positive control mice had minimal parasitaemias and cleared from the infection and survived for more than 100 days. On the other hand mice in the experimental group, experienced a prolonged suppressed parasitaemias which became patent later and caused death to all mice. Micrograph observations of parasites in the positive group showed that the parasites had adverse morphological changes due to berenil treatment which lead to cell destruction and death within 5 – 6 hours post-treatment. Likewise parasites in the experimental group too had undergone profound physical damages which caused cell death. This is the first report which shows that allicin actually induced cellular damage to haemoflagellate cells of T. evansi in vivo.